Long-Term Effects of Exposure to Ionizing Irradiation on Periodontal Health Status – The Tinea capitis Cohort Study - Sadetzki, Siegal; Chetrit, Angela; Sgan-Cohen, Harold D.; Mann, Jonathan; Amitai, Tova; Even-Nir, Hadas; Vered, Yuval (Frontiers in Public Health, 2015)
Studies among long-term survivors of childhood cancer who had received high-dose irradiation therapy of 4–60 Gy, demonstrated acute and chronic dental effects, including periodontal diseases. However, the possible effects of low to moderate doses of radiation on dental health are sparse. The aim of this study is to investigate the association between childhood exposure to low–moderate doses of ionizing radiation and periodontal health following 50 years since exposure. The study population included 253 irradiated subjects (treated for Tinea capitis in the 1950s) and, 162 non-irradiated subjects. The estimated dose to the teeth was 0.2–0.4 Gy. Dental examination was performed according to the community periodontal index (CPI). Socioeconomic and health behavior variables were obtained through a personal questionnaire. Periodontal disease was operationally defined as “deep periodontal pockets.” A multivariate logistic regression model was used for the association of irradiation status and other independent variables with periodontal status. The results showed that among the irradiated subjects, 23%, (95% CI 18–28%) demonstrated complete edentulousness or insufficient teeth for CPI scoring as compared to 13% (95% CI 8–19%) among the non-irradiated subjects (p = 0.01). Periodontal disease was detected among 54% of the irradiated subjects as compared to 40% of the non-irradiated (p = 0.008). Controlling for education and smoking, the ORs for the association between radiation and periodontal disease were 1.61 (95% CI 1.01–2.57) and 1.95 (95% CI 1.1–3.5) for ever never and per 1 Gy absorbed in the salivary gland, respectively. In line with other studies, a protective effect for periodontal diseases among those with high education and an increased risk for ever smokers were observed. In conclusion, childhood exposure to low-moderate doses of ionizing radiation might be associated with later outcomes of dental health. The results add valuable data on the long-term health effects of exposure to ionizing radiation and support the implementation of the ALARA principle in childhood exposure to diagnostic procedure involving radiation.